(untitled) (Fiep Bulletin - online, 2015)
The Project Bodies Extension Debate, developed since 2007 in public schools aims to broaden the discussion on issues related to the body and its complex socio-cultural relations that are reflected in the school environment, yet rooted to a disciplinary vision of bodies. Our proposal is based on interdisciplinary and multicultural country based on socio-anthropological studies of Le Breton (2006, 2009); understand the notion of the body as a synthesis of subject and territory of individualization, are structured means by which the processes of socialization and institution representations. This analysis began with a diagnostic workshop that directed the processes of reflection in this group from the choice of images taken from magazines where children should be represented. Identified dissatisfaction with their own body characteristics and silencing of images and speeches related to black. Thus, the project was organized into two main themes: Body and media and racial diversity: the appreciation of black. 16 workshops were developed using different forms of language, movies, cartoons, skits, group discussions etc. 106 students from the 4th and 5th years of public school in Rio de Janeiro participated. The results indicate the denial of personal characteristics such as skin color, hair type and biotype rather than a body pattern accepted by the group as ideal. In conclusion, we emphasize the speech of a mother who exemplifies the increased criticality of children from experiences in Bodies Project Debate: "The work was very good of you, my son now every time he sees the novel says it is unfair to have few blacks on TV and that right was to have half black and half white, like there is in real life. I found it funny that he noticed that the Green Lantern was black and white film put it. "